Prussia Disaggregated: The Demography of its Universe of Localities in 1871 - Sascha O. Becker; Francesco Cinnirella (Institute of Labor Economics (IZA), 2020)
We provide, for the first time, a detailed and comprehensive overview of the demography of more than 50,000 towns, villages, and manors in 1871 Prussia. We study religion, literacy, fertility, and group segregation by location type (town, village, and manor). We find that Jews live predominantly in towns. Villages and manors are substantially segregated by denomination, whereas towns are less segregated. Yet, we find relatively lower levels of segregation by literacy. Regression analyses with county-fixed effects show that a larger share of Protestants is associated with higher literacy rates across all location types. A larger share of Jews relative to Catholics is not significantly associated with higher literacy in towns, but it is in villages and manors. Finally, a larger share of Jews is associated with lower fertility in towns, which is not explained by differences in literacy.
Keywords: J13; J15; I21; N33; Z12; 330; religion; segregation; literacy; fertility; Prussia